Kajian Kadar Akrilamida dalam Kopi Arabika dengan Variasi Suhu Penyangraian: Study of Acrylamide Levels in Arabica Coffee with Variations in Roasting Temperature - Gatut Ari Wardani; Lilis Tuslinah; Eva Saefatuzzahro; Indra (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2021)
Acrylamide levels in Arabica coffee at various roasting temperatures have been determined. Coffee beans are roasted at 160°C, 180°C, and 210°C for 8 minutes. Analysis was carried out using High-Performance Liquid Chromatography (HPLC) with C-18 reversed-phase, mobile phase using methanol and 0.1% phosphoric acid solution (5:95), flow rate 1 mL/min, UV-Vis detector 198 nm wavelength. Acrylamide levels in Arabica coffee are 160°C of 14.665 ppm, 180°C of 15.973 ppm, and 210°C of 18.501 ppm. Based on the results of the acrylamide content in Arabica coffee, the higher the roasting temperature, the greater the acrylamide content. ANOVA test regarding the normality test sig value of 0.637, 0.463, and 0.637 normally distributed. Based on the homogeneity test, it was found that the variation between groups was the same or homogeneous. The results of the ANOVA test stated that there were differences in the acrylamide levels of Arabica coffee in the roasting temperature difference group and the results of the post hoc Bonferroni test found that the average differences in the roasting temperature of Arabica coffee were significantly different 160°C-180°C and 160°C-210°C.